2001
DOI: 10.1002/mrd.1131
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of cytoplasmic lipid droplets in bovine embryos and cryotolerance of embryos developed in different culture systems using serum‐free or serum‐containing media

Abstract: In this study, the quantitative fluctuation of cytoplasmic lipid droplets (LD) and cryotolerance were investigated in bovine embryos derived from in vitro-matured (IVM) and in vitro-fertilized (IVF) oocytes developed in different culture systems using serum-free or serum-containing media. The serum-free cultures were grown using IVMD101 medium in conjunction with bovine cumulus/granulosa cell (BCGC) cocultures or IVD101 medium without BCGC cocultures, and the serum-containing cultures were grown in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
260
0
27

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 308 publications
(297 citation statements)
references
References 31 publications
10
260
0
27
Order By: Relevance
“…Culture in the absence of serum results in less lipid accumulation in embryos [26]. A further finding is that embryos with less lipids, produced without serum in the medium, also cryopreserve more successfully that lipidrich embryos produced in the presence of serum [4,8,26].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Culture in the absence of serum results in less lipid accumulation in embryos [26]. A further finding is that embryos with less lipids, produced without serum in the medium, also cryopreserve more successfully that lipidrich embryos produced in the presence of serum [4,8,26].…”
Section: Discussionmentioning
confidence: 90%
“…Other works [8,26,43] showed that bovine embryos cultured without serum had more cryo-resistance, particularly when embryos were vitrified. Mucci et al [43] observed a lack of benefit from the serum on embryo development, probably as a consequence of differences in experimental conditions compared with other authors, such as the absence of co-culture during the whole development period, and the type and concentration of serum used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Crosier et al [15,16], Abe et al [3] and Abe and Hoshi [1] based on observations in morulae and blastocysts produced in vitro proposed that the presence of serum would have adverse effects on mitochondria structure, promoting lipid accumulation, thus reducing the quality and viability of the embryo. Frequently this hypothesis is used to explain survival`s decrease of embryos after cryopreservation treatments though it has not yet been proven.…”
Section: Introductionmentioning
confidence: 99%